Farmer's Preferences for Abiotic Stress Tolerance in Hybrid Versus Traditional Rice - International Food Policy Research Institute (International Food Policy Research Institute, 2014)
The survey, Farmer's Preferences for Abiotic Stress Tolerance in Hybrid versus Traditional Rice: Evidence from Bihar, India (2012-13), was designed to assess farmer's willingness to pay for drought-tolerant paddy in Bihar, India. The survey includes carefully designed discrete choice experiments and a risk experiment to collect information on demand for drought tolerance characteristics in rice and the role of both the public and the private sector in the research and development of the same. The data were collected from 576 rice-producing households in rural Bihar, as a part of a study under the Cereal Systems Initiative for South Asia (CSISA).CSISA's vision is to decrease hunger and malnutrition and to increase food and income security for resource-poor farm households in Bangladesh, India, and Nepal through the accelerated development and inclusive deployment of new and improved crop varieties, sustainable technologies and management practices, and improved policies.